Ecuadorian Indians, the Nation, and Class in Historical Perspective: Rethinking a "New Social Movement" - Clark, A. Kim (Anthropologica, 2022)
Today the Ecuadorian Indian movement is the strongest of its kind in Latin America. Such a movement may seem to indicate the declining importance of class as a category of social analysis and basis for identity, and the rise of ethnicity in its place. This article argues, however, that the gains of the Indian movement can best be understood in the context of: an historical analysis of shifting class relations and projects; a modernist state project of inclusion imposed from above (with unexpected consequences); and changing international political economic processes, reshaping the terrain on which local struggles would be carried out.